2022
DOI: 10.33448/rsd-v11i11.32184
|View full text |Cite
|
Sign up to set email alerts
|

eHealth platforms for promoting active living: a scoping review protocol

Abstract: Introduction: In increasingly aging societies, the life course towards aging should be a positive experience supported by interventions for promoting healthy lifestyles, namely through social interaction. Technological advancements, such as eHealth platforms, are becoming increasingly available and may facilitate a more autonomous life and promote active and healthy living. Objectives: To map eHealth platforms designed and used to promote autonomous life and active aging. Methods: This scoping review will foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This scoping review identified several digital services: Internet of Things technologies (wearable devices, environmental sensors) [ 37 , 40 , 41 , 45 ]; online interventions [ 29 , 34 , 35 , 38 , 39 ]; mHealth interventions [ 39 , 46 , 49 ], and gaming and exergaming [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scoping review identified several digital services: Internet of Things technologies (wearable devices, environmental sensors) [ 37 , 40 , 41 , 45 ]; online interventions [ 29 , 34 , 35 , 38 , 39 ]; mHealth interventions [ 39 , 46 , 49 ], and gaming and exergaming [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review follows the JBI methodology for scoping reviews (Peters et al, 2020) and meets the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) checklist [ 34 ]. The protocol of this review has already been published [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding older adults, research carried out internationally in the domain of Ageing in place has shown an increase in the supply of digital resources [88,89]. Specifically, ICT-based platforms that follow a person-centred approach have the potential to improve health and social care services in community settings.…”
Section: Citizen's Empowerment For Person-centred Ictmentioning
confidence: 99%
“…Specifically, ICT-based platforms that follow a person-centred approach have the potential to improve health and social care services in community settings. Such person-centred ICTs may empower citizens to actively participate in their healthcare and decision-making processes while enabling them to interact directly with healthcare and service providers about their personal health concerns, thereby promoting active ageing [86][87][88]. Thanks to the use of home automation and the Internet of Things, "Smart Homes" improve the quality of life of older adults and people with disabilities, allowing them to live healthier and more independently and supporting healthcare workers in their care [90].…”
Section: Citizen's Empowerment For Person-centred Ictmentioning
confidence: 99%